2021
DOI: 10.1038/s41408-021-00514-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute promyelocytic leukemia current treatment algorithms

Abstract: In 1957, Hillestad et al. defined acute promyelocytic leukemia (APL) for the first time in the literature as a distinct type of acute myeloid leukemia (AML) with a “rapid downhill course” characterized with a severe bleeding tendency. APL, accounting for 10–15% of the newly diagnosed AML cases, results from a balanced translocation, t(15;17) (q22;q12-21), which leads to the fusion of the promyelocytic leukemia (PML) gene with the retinoic acid receptor alpha (RARA) gene. The PML–RARA fusion oncoprotein induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 77 publications
1
106
0
7
Order By: Relevance
“… (A) Giemsa‐stained metaphase spread, acquired after 48 h of incubation in culture media. (B) Metaphase spread from a non‐stimulated culture of peripheral blood sample demonstrating 47, XY, +8, del [ 9 ] (q21.1q22.1); t (15;17) (q24; q21) …”
Section: Case Presentationmentioning
confidence: 99%
“… (A) Giemsa‐stained metaphase spread, acquired after 48 h of incubation in culture media. (B) Metaphase spread from a non‐stimulated culture of peripheral blood sample demonstrating 47, XY, +8, del [ 9 ] (q21.1q22.1); t (15;17) (q24; q21) …”
Section: Case Presentationmentioning
confidence: 99%
“…In some FLT3-ITD+ APL patients, it was observed that the presenting clone at relapse lost the FLT3-ITD mutations or other passenger mutations that were present at diagnosis, indicating the existence of a pre-leukemic PML-RARA-expressing clone that survived RA/chemotherapy and reinitiated APL [37]. The combination of ATRA and As 2 O 3 has greatly reduced the rate of relapse and improved the lives of APL patients [38], and represents one of the most successful targeted cancer therapies available today, second in line only to TKI treatment in CML.…”
Section: Pml-raramentioning
confidence: 99%
“…Acute promyelocytic leukemia (APL) with PML‐RARA accounts for 10%–15% of the newly diagnosed acute myeloid leukemia (AML) cases (Arber et al, 2017; Yilmaz et al, 2021). The onset of APL is commonly associated with disseminated intravascular coagulation (DIC) and patients have a high mortality rate if not treated promptly.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of APL is commonly associated with disseminated intravascular coagulation (DIC) and patients have a high mortality rate if not treated promptly. All‐trans retinoic acid (ATRA) has been used to induce the immediate improvement of APL and control DIC (Yilmaz et al, 2021). In earlier studies, others have shown that early administration of ATRA (<24 h) and vigorous correction of hemostatic imbalance are keys to reducing early death in APL patients (Gill et al, 2021).…”
Section: Introductionmentioning
confidence: 99%